A quasi-experimental study on the impact of simulation-based learning on toefl performance in undergraduate nursing programs - Irianto, Dhaniel Prasetyo; Nurniati, Emi (Institute of Computer Science (IOCS), 2025)
This study investigates the effectiveness of Simulation-Based Learning (SBL) in improving the TOEFL performance of undergraduate nursing students, a growing need in nursing education due to increasing global competency demands. The research aims to determine the impact of SBL on overall TOEFL scores and its sectional components listening, structure, and reading as well as to compare these outcomes with conventional TOEFL instruction. A quasi-experimental design with a non-equivalent control group was employed, involving 60 nursing students from the Faculty of Health at Noor Huda Mustofa University. The experimental group received four sessions of SBL-based instruction, while the control group followed traditional TOEFL preparation. TOEFL ITP-style tests were administered as pre- and post-tests to assess performance changes. The results showed significant score improvements in both groups; however, the experimental group achieved substantially higher gains across all components. Paired t-tests confirmed significant within-group improvements, and independent t-tests revealed significant post-test differences favoring the SBL group, with the largest effect size found in the structure component. The findings indicate that SBL creates an engaging, immersive, and cognitively demanding learning environment capable of enhancing academic English proficiency more effectively than conventional methods. This study concludes that SBL is a relevant and effective pedagogical strategy for strengthening TOEFL readiness and supporting global competency development in nursing education.